2021
DOI: 10.1016/s0140-6736(21)01744-x
|View full text |Cite|
|
Sign up to set email alerts
|

Inhaled budesonide for COVID-19 in people at high risk of complications in the community in the UK (PRINCIPLE): a randomised, controlled, open-label, adaptive platform trial

Abstract: Background A previous efficacy trial found benefit from inhaled budesonide for COVID-19 in patients not admitted to hospital, but effectiveness in high-risk individuals is unknown. We aimed to establish whether inhaled budesonide reduces time to recovery and COVID-19-related hospital admissions or deaths among people at high risk of complications in the community. Methods PRINCIPLE is a multicentre, open-label, multi-arm, randomised, controlled, adaptive platform trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
233
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(241 citation statements)
references
References 23 publications
2
233
1
5
Order By: Relevance
“…This study is only the second study to show an important treatment benefit for a repurposed drug in the early treatment population. 13 Our findings represent the complete analysis of the trial after the DSMC recommended stopping the active fluvoxamine group and all 28-day follow-up of randomly assigned patients. Given fluvoxamine's safety, tolerability, ease of use, low cost, and widespread availability, these findings might influence national and international guidelines on the clinical management of COVID-19.…”
Section: Discussionmentioning
confidence: 84%
“…This study is only the second study to show an important treatment benefit for a repurposed drug in the early treatment population. 13 Our findings represent the complete analysis of the trial after the DSMC recommended stopping the active fluvoxamine group and all 28-day follow-up of randomly assigned patients. Given fluvoxamine's safety, tolerability, ease of use, low cost, and widespread availability, these findings might influence national and international guidelines on the clinical management of COVID-19.…”
Section: Discussionmentioning
confidence: 84%
“…A second open label trial, the Platform Randomised Trial of Treatments in the Community for Epidemic and Pandemic Illnesses (PRINCIPLE) study 15 also suggested a possible effect of inhaled budesonide, with a benefit in time to first self-reported recovery of 2.94 days (95% bayesian credible interval 1.19 to 5.12 days) (11.8 days (10.0 to 14.1 days) in the budesonide group v 14.7 days (12.3 to 18.0 days) in the usual care group; hazard ratio 1.21 (95% bayesian credible interval 1.08 to 1.36)). The observed effect on symptom resolution was equally apparent among participants aged 50 to 65 years with comorbidities, and in people older than 65 years.…”
Section: Discussionmentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t community Inhaled Budesonide [13,14] Possibly Colchicine [12] Type 5a…”
Section: -50%mentioning
confidence: 99%